1.99 Ga mafic magmatism in the Rona terrane of the Lewisian Gneiss Complex in Scotland - Baker, T.; Prave, A.; Spencer, Christopher (Elsevier BV, 2019)
The Scourie dyke swarm has long been important to unravelling the geological history of the Lewisian Gneiss Complex (LGC) and the North Atlantic Craton. Recent dating has documented that the majority of those dykes were emplaced between c. 2418–2375 Ma. Here we show that a quartz dolerite dyke in the Rona Terrane of the LGC has a U-Pb zircon age of 1989.08 +4.3/-0.99 Ma. This is the first mafic dyke to be dated from the Rona terrane, the southernmost of those proposed for the terrane model of the LGC. Our new age also overlaps with the c. 1992 Ma age of a previously dated olivine gabbro dyke in the Northern region of the LGC and shows that the LGC contains at least three, and possibly four, temporally discrete episodes of Palaeoproterozoic mafic magmatism: The Scourie dyke swarm ‘sensu stricto’ at c. 2.4 Ga; a suite of younger dykes at c. 1.99 Ga, referred to here as the Strathan dyke swarm; and the c. 1.99–1.90 Ga mafic rocks that are part of the Palaeoproterozoic Loch Maree Group. A c. 2.04 Ga dyke in the Assynt terrain may be part of the younger suite of dykes or perhaps records a temporally separate event. Crucially, our new age data demonstrate that suites of mafic dykes emplaced across the mainland LGC are similar in age and supports the correlation of structural and metamorphic features across that Complex.